2003
DOI: 10.1364/oe.11.003304
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of FPU recurrence in a fiber ring laser

Abstract: Abstract:We report on the experimental observation of Fermi-Pasta-Ulam (FPU) recurrence in a passively mode-locked fiber ring laser. The spectral sidebands of a CW component generated due to the modulation instability grow up periodically as a result of the reversibility of the effect, demonstrating the existence of FPU recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…If the background noise of a certain frequency fulfills the lasing condition, it could also start to lase and form a CW component in the soliton spectrum. We note that coexistence of solitons with CW is a generic effect of the soliton fiber lasers, and the phenomenon was reported by several authors [36,37]. Linear waves are intrinsically unstable in the cavity due to the modulation instability.…”
Section: Mechanism Of the Multiple Soliton Generation And Soliton Enesupporting
confidence: 71%
“…If the background noise of a certain frequency fulfills the lasing condition, it could also start to lase and form a CW component in the soliton spectrum. We note that coexistence of solitons with CW is a generic effect of the soliton fiber lasers, and the phenomenon was reported by several authors [36,37]. Linear waves are intrinsically unstable in the cavity due to the modulation instability.…”
Section: Mechanism Of the Multiple Soliton Generation And Soliton Enesupporting
confidence: 71%
“…Indeed, it has been recently predicted and experimentally observed that third-order dispersion induced losses into Cherenkov radiation may lead to irreversible energy dissipation of the pump field, which ultimately breaks the FPU recurrence [27,28]. As a matter of fact, experiments carried out so far in nonlinear fiber optics have not been able to demonstrate FPU recurrence beyond a single spatial period [15][16][17][18][19]. In addition, recent studies regarding noise-induced MI have highlighted the complex dynamics associated with the onset stage of noise amplification [29,30] and their intriguing links with the mechanisms underlying rogue waves formation in optical fiber [4,31].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the NLSE model predicts a fully reversible or spatially periodic power exchange among the pump, the initial modulation sidebands and all their harmonics. This process can be described in terms of exact solutions of the NLSE [9][10][11][12], and it has been experimentally observed in deep water waves [13,14], nonlinear optical fibers [15][16][17][18][19][20], nematic liquid crystals [21], magnetic film strip-based active feedback rings [22], and bimodal electrical transmission lines [23]. Useful physical insight into the qualitative dynamics of FPU recurrence, such as for example the presence of separatrix solutions, or the dependence of the FPU recurrence period upon the input relative phase between the pump and the initial modulation sidebands, may be obtained by using a three-wave truncation which leads to a fully integrable, one-dimensional equivalent particle model [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…If the background noise of a certain frequency fulfills the lasing condition, it could also start to lase and form a CW component in the soliton spectrum. We note that coexistence of solitons with CW is a generic effect of the soliton fiber lasers, and the phenomenon was reported by several authors [89,90]. It turns out that the multiple soliton formation in the laser is in fact caused by the peak power clamping effect of the cavity.…”
Section: Numerical Simulations and Resultssupporting
confidence: 70%